Impact of strategic management, corporate social responsibility on firm performance in the post mandate period: Evidence from India - Nayan Mitra (International Journal of Corporate Social Responsibility (JCSR), 2021)
Corporate Social Responsibility (CSR) is like a chameleon, that changes its colour according to the context it is in. In the developed economy, it takes the form of sustainability and/ or philanthropy, whereas, in emerging economies, it speaks the language of religious, political and/or mandated CSR. India, in recent times came into the limelight with its mandated CSR policy that was incorporated into its Companies Act 2013, which became operational from the financial year 2014 - 2015. Mandated CSR is thus a new area of study that is based on the philosophy that "CSR should contribute to the national agenda in emerging economies", under some statutory guidelines as laid down by the Government.
Keywords: 650; Corporate social responsibility; CSR; Strategic management; Internal orientation; External orientation; CSR intent; CSR management; Industrial standards; CSR communication; Community orientation; Market orientation; Supply chain orientation; Mandated CSR; Section 135; Schedule VII; India; Empirical study; Firm performance; Emerging economies; Intangible benefits; Reputation; Image; Scale development; Corporate Social Responsibility; Strategisches Management; Wirkungsanalyse; Unternehmenserfolg; Entwicklungsländer; Indien